1990
DOI: 10.1007/bf01402177
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and risks of antifibrinolytic therapy in the management of ruptured intracranial aneurysms

Abstract: One hundred patients with a verified subarachnoid haemorrhage were studied in a double blind, placebo-controlled trial at a single centre to determine the value and relative risks of tranexamic acid (TXA) in the management of ruptured intracranial aneurysms. The incidence of recurrent haemorrhage between active and placebo groups was identical (12%) and the mortality from recurrent haemorrhage was 7% and 5%, respectively. The overall incidence of cerebral infarction before surgery, at discharge and at 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…144 Similar findings were reported by Kassell et al 240 in a nonrandomized, controlled study; a 40% reduction in rebleeding in patients receiving antifibrinolytic therapy was offset by a 43% increase in focal ischemic deficits. In a double-blind, placebo-controlled trial of tranexamic acid, 249 there was no difference in rebleeding between groups, and an increase in cerebral ischemia was seen for treated patients, although the sample size was not sufficient to demonstrate significance. Retrospective studies 250,251 have shown similar results regardless of the duration of antifibrinolytic therapy with either epsilon aminocaproic acid (36 g/d) or tranexamic acid (6 to 12 g/d).…”
Section: Medical Measures To Prevent Rebleeding After Sahmentioning
confidence: 93%
“…144 Similar findings were reported by Kassell et al 240 in a nonrandomized, controlled study; a 40% reduction in rebleeding in patients receiving antifibrinolytic therapy was offset by a 43% increase in focal ischemic deficits. In a double-blind, placebo-controlled trial of tranexamic acid, 249 there was no difference in rebleeding between groups, and an increase in cerebral ischemia was seen for treated patients, although the sample size was not sufficient to demonstrate significance. Retrospective studies 250,251 have shown similar results regardless of the duration of antifibrinolytic therapy with either epsilon aminocaproic acid (36 g/d) or tranexamic acid (6 to 12 g/d).…”
Section: Medical Measures To Prevent Rebleeding After Sahmentioning
confidence: 93%
“…Clinical trials and large observational studies indicate that these agents reduce the frequency of rebleeding after aneurysmal subarachnoid hemorrhage but increase the frequency of delayed cerebral ischemia and other thrombotic complications, resulting in no overall benefit on outcome. [72][73][74] Aprotinin is a polypeptide that inhibits the action of several serine proteases (including plasmin and kallikrein) by forming reversible enzyme-inhibitor complexes. 57 By inhibiting kallikrein, aprotinin indirectly inhibits the formation of activated factor XII, which disrupts coagulation.…”
Section: Hemostatic Agents: Therapeutic Optionsmentioning
confidence: 99%
“…However, there was no effect on the overall outcome as a result of an increased incidence of DCI, and impeded recovery from DCI, if this occurred (Vermeulen et al, 1984;Roos, 2000;Roos et al, 2003). As tranexamic acid does not influence the rate of cerebral vasospasm, direct hemostatic effects are a more plausible explanation for the increased incidence of DCI (Tsementzis et al, 1990). Therefore, it seems that the incidence and recovery from DCI can be influenced by drugs without a clear effect on vasospasm.…”
Section: Introductionmentioning
confidence: 96%